Analysis of concrete characteristics with the incorporation of construction waste aggregates - Monteiro Costa Sbampato Resende, Gustavo; Antonio Correa Gomes, Diogo; Rodrigues, Adriano; Pereira Vilela, Alan; Pereira Rodrigues, Tales (Revista Brasileira de Engenharia de Biossistemas, 2022)
In order to reuse civil construction materials, research is carried out to obtain an efficient recycled concrete, promoting sustainability. The objective of this work is to compare the compressive strengths of the concrete specimen, with conventional and recycled aggregates, as well as the influence of granulometry on the strength and physical properties of the aggregates. For this purpose, aggregates from civil construction waste were incorporated into the concrete, replacing part of the coarse aggregates. Specimens were made with the following replacement percentages: 0%, 5%, 10%, and 15%, for multiple comparisons. The control group had no replacement of conventional aggregates by recycled ones (0%). The following tests were carried out: granulometric, density, water absorption, compressive strength, and slump test. Recycled concrete presents itself as a viable option in non-structural concretes, presenting greater efficiency in the compressive strength test at granulometry of 4.75 – 9.50 mm, with 15% incorporation.